1985
DOI: 10.1111/j.1365-2591.1985.tb00449.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of root canal preparation on the shape of the curved root canal

Abstract: Summary. This study reports the effect of the step‐bad enlargement technique of root canal preparation on the shape of the curved root canal of extracted human teeth. This was achieved by superimposing tracings made from photographic prints obtained by radiographs of teeth before canal preparation, after apical preparation and after coronal flaring. After apical preparation, the root canal sometimes demonstrated an hour‐glass shape. Flaring the coronal portion of the canal was often successful in opening out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
32
0
1

Year Published

1991
1991
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 15 publications
0
32
0
1
Order By: Relevance
“…According to the results of the present study, all systems removed more material on the outer side of the curvature in the apical 1-3 mm from the apex. Previously published reports (10)(11)(12) have also confirmed that any instrument in a curved canal always tries to straighten itself. It therefore cuts straight ahead and does most of its work removing material on the outside of the curve in the apical region.…”
Section: Discussionmentioning
confidence: 60%
“…According to the results of the present study, all systems removed more material on the outer side of the curvature in the apical 1-3 mm from the apex. Previously published reports (10)(11)(12) have also confirmed that any instrument in a curved canal always tries to straighten itself. It therefore cuts straight ahead and does most of its work removing material on the outside of the curve in the apical region.…”
Section: Discussionmentioning
confidence: 60%
“…This model guarantees a high degree of reproducibility and standardization of the experimental design (11,18,19), but it might not always reflect the action of the instruments in root canals of real teeth (20). Some concerns have been expressed regarding the differences in hardness between dentin and resin (21).…”
Section: Discussionmentioning
confidence: 98%
“…Attempts were made to also study preparation size 60/.04 to allow direct comparisons with previous data using the same method (12)(13)(14) but instrumentation to size 60/.04 invariably resulted in apical perforation in curved root samples. From a clinical perspective, although increasing apical preparation sizes in curved root canal systems may allow for more effective irrigation, this is not always practical or desirable because of the potential for root perforation, root fracture, or weakening (7,15,30). In cases where an enlarged apical preparation is desired in curved root canals, the Lightspeed file system may offer an advantage over a continuous tapered file system because the cutting edge does not remove cervical root structure during the apical preparation, thus minimizing the excess removal of tooth structure (7).…”
Section: Discussionmentioning
confidence: 99%